The Star, 26 March 2007 - Looi, Elizabeth (Star Publications (Malaysia) Berhad, 2007)
Learner driver must show they have acquired defensive driving skills before they can qualify for a driving licence under a new curriculum to be introduced by the Road Transport Department.